ASISTENSI MENGAJAR DALAM MENINGKATKAN PEMAHAMAN LAPORAN KEUANGAN PERUSAHAAN JADA DI SMA BUNDA HATI KUDUS JAKARTA - Maria Bernadet Pek; Merry Susanti (Jurnal Serina Abdimas, 2026)
In the midst of digital era, the entrepreneurial spirit of the younger generation is growing rapidly. With easy access to technology, many young people are innovating to create new business opportunities. However, despite these advancements, a significant number of students continue to exhibit low levels of financial literacy, particularly in their understanding of the proper preparation of financial statements, which serve as the foundation for systematic financial management. The Teaching Assistantship in Educational Units program, as part of the Merdeka Belajar Kampus Merdeka initiative, serves as a platform for university students to contribute directly to improving the quality of education by sharing their knowledge with high school students. The financial reports taught to the students in this activity include the income statement, statement of changes in equity, and statement of financial position. This teaching assistantship is conducted at SMA Bunda Hati Kudus Jakarta every Monday from 12.20 p.m. to 2.20 p.m., from August to November of 2025. The participants of this activity are students from class XII-I with a specialization in design. This teaching is based on a project-based learning approach, which is expected to help students gain a deeper understanding of accounting concepts, particularly in preparing financial reports for service-based companies. Through this activity, it is expected that the students of SMA Bunda Hati Kudus Jakarta can use their insights of accounting concepts and financial reporting in their future studies or careers, so that they are prepared to face any financial challenges they might encounter in the future. Di tengah kehidupan era digital, semangat kewirausahaan generasi muda semakin berkembang pesat. Dengan mudahnya akses terhadap teknologi, banyak anak muda yang berinovasi untuk menciptakan peluang bisnis baru. Namun, di balik kemajuan tersebut, masih banyak pelajar yang memiliki tingkat literasi finansial yang rendah, termasuk dalam memahami cara menyusun laporan keuangan secara benar sebagai dasar pengelolaan keuangan secara sistematis. Kegiatan Asistensi Mengajar di Satuan Pendidikan, sebagai bagian dari program Merdeka Belajar Kampus Merdeka merupakan sebuah wadah bagi mahasiswa untuk berkontribusi langsung guna meningkatkan kualitas pendidikan dengan berbagi pengetahuan kepada siswa di sekolah. Laporan keuangan yang diajarkan kepada siswa/i dalam kegiatan ini terdiri dari laporan laba rugi, laporan perubahan modal, dan laporan posisi keuangan. Kegiatan asistensi mengajar ini dilaksanakan di SMA Bunda Hati Kudus Jakarta setiap hari Senin pukul 12.20 – 14.20, sejak bulan Agustus 2025 sampai dengan bulan November 2025. Peserta dari kegiatan ini adalah siswa/i kelas XII-I dengan penjurusan di bidang desain. Pengajaran dilakukan berdasarkan dengan project-based learning yang diharapkan dapat membantu siswa/i agar memahami lebih dalam mengenai konsep akuntansi, terutama pada penyusunan laporan keuangan perusahaan jasa. Dengan diadakannya kegiatan ini, diharapkan siswa/i SMA Bunda Hati Kudus Jakarta dapat menggunakan wawasan mengenai konsep akuntansi dan pelaporan keuangan dalam studi maupun karir mereka selanjutnya sehingga siap untuk menghadapi tantangan keuangan yang mungkin dihadapi di masa depan.